The crowdfunding model, collective intelligence, and open innovation - Sangjae Pyo; Hyoung Ryul Ma; Sumi Na; Dong-Hoon Oh (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
In recent years, crowdfunding has attracted the attention of tech startups. It has become a good alternative way to readily raise funds, especially during the early startup stages. However, in the case of mass intelligence, it is quite difficult to ensure the accuracy and reliability of knowledge. Individual investors who are not experts in science and technology often face difficulties investing in technology companies. In this regard, a new type of collective intelligence formed by accredited professionals needs to be attempted. This paper explores an alternative crowdfunding model for enhancing access to technology investments by the general population through an investor acceptance model. We developed an investor acceptance model to examine how the crowdfunding model involving scientists and engineers is adopted by individual investors using survey data from the general population. The results revealed that individual investors have a positive attitude towards investing through the crowdfunding model when they perceive that the information provided by a group of scientific experts is useful. We found that the perceived usefulness of the information from scientists and engineers is affected by the perceived quality of the information and perceived credibility of the scientists and engineers. We also suggest a basic concept for the crowdfunding model utilizing the collective intelligence of scientists and engineers for tech startups. The results could suggest a policy direction for promoting innovation.
Keywords: 650; collective intelligence; crowdfunding; engineers; fund-raise; individual investor; investment; open innovation; scientists; startups; technology